Understanding Maqāṣid al-Sharī‘ah - Tariq Al-Timimi (International Institute of Islamic Thought, 2017)
Musfir al-Qahtani’s translated book is a recent contribution on the contemporary relevance of maqāṣid al-Sharī‘ah. After a lengthy introduction in which he outlines some technical aspects of the subject, he turns to their relevance for issuing fatwas (e.g., “cultural development,” “religious extremism,” and “the Muslim mindset”) before rounding-off with what he calls the “goal awareness crisis.” Helpfully, the reader is provided with a synopsis at the beginning of every chapter. The book is divided into five main chapters. The introduction seeks to establish a definition for the maqāṣid al-Sharī‘ah while drawing attention to how others have referred to them. The reader is then briefly presented with the textual and “logical” (read: theological) arguments in favor of ta‘līl al-aḥkām (determining the ratio decidendi of rulings), a fundamental query in the quest to establish the field’s validity. Neither section is very detailed, and it soon becomes clear that the author wrote this book for activists who want to understand what the maqāṣid are and what relevance they hold for their cause. Having established the proofs for the concept, al-Qahtani turns to the maqāṣid’s meta-structure. There is nothing original in this chapter, as al-Izz bin Abdussalam (d. 1262), al-Shatibi (d. 1388), Ibn al-Qayyim (d. 1350), and the other usual figures are cited. It is much to the author’s credit, however, that he refers (albeit once and almost just as a gesture) to Mustafa Shalabi (d. 1997), who has been largely overshadowed by other scholars despite his major contributions to the field of Islamic law and legal theory, most notably in his 1944 Azhar ‘ālimīyah thesis Ta‘līl al-Aḥkām ...